VACCINATION AGAINST CORONAVIRUS INFECTION IN FERGANA REGION FOR THE PERIOD 2021-2022 - Ruzibaeva E.R; Mamatkulova M.T (Scholar Express Journals, 2023)
Immunization is one of the key components of primary health care, and the right to immunization is an inalienable human right. Vaccines are also crucial for preventing and suppressing outbreaks of infectious diseases. They are at the heart of global health security and will remain a vital tool in the fight against antimicrobial resistance
Keywords: vaccination; booster; pandemic; Ferghana region